A comparative study between conformal and intensity modulated radiation therapy in the treatment of primary nasopharyngeal carcinomas - Karim Nabil Mashhour; Ehsan Gamal Eldin Elchoneimy; Mahmoud Fawzy Elbestar; Mohamed Abdullah Hassan (Cairo : Karim Nabil Mashhour, 2012)
The study is a comparative randomized study between two groups of patients, the aim of which is to compare 3D conformal radiation therapy (3D-CRT) and intensity modulated radiation therapy (IMRT) as newer modalities in treating nasopharyngeal carcinomas; evaluating and comparing both techniques as regard their efficacy on tumor response, local control and treatment related toxicity as a dosimetric comparison between both techniques
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Oncolog-Clinical
Issued also as CD
Keywords: 3D-conformal; IMRT; Nasopharynx cancer